Dynamic Light Regulation of Translation Status in Arabidopsis thaliana - Bailey-Serres, Julia; Juntawong, Piyada (Frontiers in Plant Science, 2012)
Light, a dynamic environmental parameter, is an essential regulator of plant growth and development. Light-regulated transcriptional networks are well documented, whereas light-regulated post-transcriptional regulation has received only limited attention. In this study, dynamics in translation of cytosolic mRNAs were evaluated at the genome-level in Arabidopsis thaliana seedlings grown under a typical light / dark diurnal regime, shifted to darkness at midday and then re-illuminated. One-hour of unanticipated darkness reduced levels of polyribosomes (polysomes) by 17% in a manner consistent with inhibition of initiation of translation. This down-regulation of protein synthesis was reversed within 10 minutes of re-illumination. Quantitative comparison of the total cellular population of transcripts (the transcriptome) to those associated with one or more 80S ribosome (the translatome) identified over 1600 mRNAs that are differentially translated in response to light availability. Unanticipated darkness limited transcription and translation of mRNAs encoding components of the photosynthetic machinery. Many mRNAs encoding proteins associated with the energy demanding process of protein synthesis were stable but sequestered in the dark, in a rapidly reversible manner. A meta-analysis determined these same transcripts were similarly and coordinately regulated in response to changes in oxygen availability. The dark and hypoxia translationally repressed mRNAs lack highly supported candidate RNA-regulatory elements but are characterized by G+C-rich 5’-untranslated regions. We propose that dynamic regulation of the translational status of a subset of cellular mRNAs serves as a general energy conservation mechanism.